Trois zones de coconstruction de savoirs professionnels issues des médiations de débats en groupe - Joëlle Morrissette; Sylvie Guignon (Communiquer)
This paper presents an analytical framework of teacher professional knowledge, developed from the analysis of teacher’s conversations during a research-training project. Based on the analysis of their conversational negotiations around practical cases, this framework enlightens the professional group activity by identifying three areas of knowledge, “shared”, “accepted” and “contested”, which frames the territory of their practice. We expose this framework’s value for scientific production of knowledge on a professional activity and for the professional development of practitioners. Finally, we examine the conditions of implementing a kind of intervention that supports those two aims, focusing in particular on the mediations to be mobilized in order to gain access to the knowledge of a professional practice based on the reflexivity of the practitioners, and we highlight the contribution of this framework for scientific communities – especially the communication domain – and the professional ones.